Rebranding de la marca de cerveza artesanal “Maita” - Santolalla Esteban, Silvia Ximena (2023)
Maita is a craft beer brand created in January 2021 by three university students. It is present on the social networks Instagram, Facebook and Tik Tok which are the sales channels. The rebranding process was carried out with the purpose of making the brand more attractive to connect with the target audience and thus position it in the market. The procedure is understood from the constant feedback with the owners of the brand, consultancies and validations with experts from the Communication career. The main objective is to successfully create a new concept so that the brand maintains its creative base and integrate it into the visual identity. The materials made include the renewal of the logotype, typography, color palette, the label for the product and the creation of graphics for publications.